Photocatalytic degradation of phenol over highly visible-light active BiOI/TiO2nanocomposite photocatalyst - Natkritta Boonprakob (2018)
© 2017, Chulalongkorn University 1. All rights reserved. BiOI/TiO 2 nanocomposites were successfully prepared by the two-step method, co-precipitation/solvothermal method. The amount of BiOI in the composites were varied as 0, 5.0, 7.5, 10.0 and 12.5 mol%. XRD results exhibited sharp and narrow diffraction peaks of both BiOI and TiO 2 in all composite samples. Morphologies of as-prepared samples consisted of spherical shapes of TiO 2 and nanosheets of BiOI. Diffuse Reflectance UV–visible (DR–UV–vis) spectra of composites drastically shifted into the visible range and the reduced band gap energies were observed. The composites obviously showed an enhanced phenol degradation of ca. 6 times higher than that of pure BiOI, pure TiO 2 and Degussa P25. The maximum photocatalytic activity of ca. 68% was found for 10.0 mol% BiOI/TiO 2 nanocomposite because of its increased visible light harvesting ability and its efficient electron–hole separation efficiency as observed from DR–UV–vis and photoluminescence spectra results.